Probióticos como alternativa de prevención de caries dental en pacientes pediátricos. - Escobar Noboa, Ana Belén (2025)
Probiotics are live microorganisms implicated in various health-related fields since their discovery. When administered in sufficient quantities, they enhance an individual's health. However, in dentistry they also have their importance, since they have been related to beneficial effects on oral health, thus, they take importance in the prevention of caries, especially in pediatric patients, since their consumption in milk drinks or food supplements is easy to access. The objective of this research work was to identify the action of probiotics as a preventive method of dental care in pediatric patients. The methodology was PRISMA, selecting and exclusion of articles that allowed answering the PICO question. The study identified the action of probiotics as an alternative method for the prevention of caries, finding that, through regulation of the immune response, modulation of pH, or competition for nutrients in strains such as Streptococcus dentist, Lactobacillus rhamnosus, Lactobacillus casei, Lactobacillus reuteri, they allow the pediatric host to recover the balance of the oral microbiota, preventing dental caries. It also highlights that the sources of probiotics for consumption by pediatric patients are mostly in the form of yogurt, tablets, beverages, probiotic supplements, fermented foods, as well as ice cream or chewing gum.